Market Research for Baby Shoes Product Development Strategy: A Case Study of Vinsky Baby - Johan Hendri Prasetyo; Vinska Devianti; Fildzah Nurdima (Prodi Magister Manajemen Universitas Dirgantara Marsekal Suryadarma, 2026)
The baby product market has experienced significant growth in recent years, creating opportunities for small and medium enterprises (SMEs) to develop innovative and competitive products. However, increasing competition requires businesses to better understand consumer preferences and market dynamics in order to design products that meet customer needs. This study aims to analyze consumer preferences and identify market opportunities to support the product development strategy of baby shoes for the Vinsky Baby business. The research employed a market research approach using a descriptive qualitative design, combining survey data and focus group discussions (FGD) to obtain insights into consumer perceptions, product expectations, and purchasing considerations. The findings indicate that consumer purchasing decisions for baby shoes are strongly influenced by comfort, safety, practicality, and design simplicity. Parents tend to prefer baby shoes made from soft and breathable materials that support baby foot development and provide comfort during daily activities. In addition, minimalist designs and neutral colors are considered attractive because they are versatile and suitable for various baby clothing styles. Practical product features, such as Velcro fastening systems, are also preferred due to their convenience for parents. The results further suggest that businesses must strengthen product differentiation and improve digital marketing strategies to increase competitiveness in the baby footwear market. Overall, the study demonstrates that market research plays an important role in generating consumer insights that guide product attribute selection and product development strategies. These insights can support SMEs in designing products that better align with consumer needs and market trends, thereby enhancing their ability to compete in the growing baby product industry.